Analisis Pengaruh Kondisi Tanah pada Gunung Aktif dan Tidak Aktif Terhadap Hasil Pertumbuhan Kopi - Adisty Pyrenia; Putri Wihatma Andianti; Lailyatul Mukarromah; Sudarti ,; Trapsilo Prihandono (Jurnal Ilmiah Wahana Pendidikan, 2023)
Coffee is currently one of the leading agricultural commodities that has a significant contribution to the Indonesian economy, namely as a foreign exchange earner, a source of income for farmers, a producer of industrial raw materials, job creation and regional development. The data used in this study are mostly secondary data, where secondary data are theories taken from several related journals. The purpose of this research was to obtain the effect of soil conditions from active and inactive mountains on coffee growth. Obtainable results in Soil formed by active volcanic eruptions is often rich in essential minerals and nutrients. This can provide abundant resources for coffee plants to grow properly. Whereas inactive mountains tend to have lower minerals and nutrients. Thus, in cultivating coffee it is also necessary to pay attention to soil and environmental conditions as a whole to get maximum coffee plant production.